The first canid from the Gray Fossil Site in Tennessee: new perspective on the distribution and ecology of Borophagus. (November 2022) - Bōgner, Emily; Samuels, Joshua X.
Abstract: Borophagus is the terminal genus of the highly diverse and successful subfamily, Borophaginae. Skeletal remains of this bone-crushing canid are most commonly found in transitional or grassland environments across North America between Late Miocene–Middle Pleistocene, but are rare or absent in forested habitats. Here, we describe a humerus from the Gray Fossil Site of Tennessee, which is the first occurrence of this genus in a heavily forested ecosystem. The distinct limb proportions of Borophagus suggest the genus may have been well suited for a closed habitat like the Gray Fossil Site, contrary to where a majority of their fossils have been previously found. This discovery documents the first pre-Pleistocene occurrence of a canid in the Appalachian region of the eastern United States.